A Microfluidic Design for Quantitative Measurements of Shear Stress-Dependent Adhesion and Motion of Dictyostelium discoideum Cells - Sepideh Fakhari; Clémence Belleannée; Steve J. Charrette; Jesse Greener (Biomimetics)
Shear stress plays a crucial role in modulating cell adhesion and signaling. We present a microfluidic shear stress generator used to investigate the adhesion dynamics of Dictyostelium discoideum, an amoeba cell model organism with well-characterized adhesion properties. We applied shear stress and tracked cell adhesion, motility, and detachment using time-lapse videomicroscopy. In the precise shear conditions generated on-chip, our results show cell migration patterns are influenced by shear stress, with cells displaying an adaptive response to shear forces as they alter their adhesion and motility behavior. Additionally, we observed that DH1-10 wild-type D. discoideum cells exhibit stronger adhesion and resistance to shear-induced detachment compared to phg2 adhesion-defective mutant cells. We also highlight the influence of cell density on detachment kinetics.